Favorable Outcomes and Anti-TNF Durability After Addition of an Immunomodulator for Anti-Drug Antibodies in Pediatric IBD Patients. Issue 4 (19th May 2020) - Colman, Ruben J; Portocarrero-Castillo, Andrea; Chona, Deepika; Hellmann, Jennifer; Minar, Phillip; Rosen, Michael J
Abstract: Background: Anti-drug antibodies (ADAs) to anti-tumor necrosis factor alpha (anti-TNF) drugs are associated with increased drug clearance and loss of response. We aimed to assess the effectiveness of starting an immunomodulator (IM) drug in patients with newly detected ADAs on anti-TNF monotherapy. Methods: We reviewed the medical records of pediatric patients with inflammatory bowel disease on infliximab or adalimumab monotherapy with first-time detection of significant ADAs between 2014 and 2018. Patients who started an IM within 3 months of ADA detection were compared with those who did not (No-IM). Outcomes included steroid-free clinical and biochemical remission on the same anti-TNF, anti-TNF durability, and ADA reversal. Results: We identified 89 patients with ADAs: 30 IM patients and 59 No-IM patients. The initial anti-TNF was stopped shortly after ADA detection in 36% of the No-IM patients vs none of the IM patients, driving longer survival on the initial anti-TNF in the IM group ( P = 0.005). At 12 months, steroid-free clinical and biochemical remission on the same anti-TNF occurred in 53.9% of the IM group vs 26.8% in the No-IM group ( P = 0.025). Drug levels rose higher ( P = 0.003) and ADA levels fell farther ( P = 0.037) in the IM group than in the No-IM group. Baseline ADA level predicted ADA reversal in the No-IM patients with an area under the receiver operating characteristic of 0.79 ( P = 0.006). An ADA level <329 ng/mL had a 76.2% sensitivity and an 83.3% specificity for ADA reversal without IM. Conclusions: Pediatric patients with inflammatory bowel disease on anti-TNF monotherapy who started an IM for significant ADA levels exhibited longer anti-TNF durability and a higher likelihood of steroid-free clinical and biochemical remission on the same anti-TNF. Patients not treated with an IM were unlikely to reverse ADAs >329 ng/mL.